Effect of soft base layer on scratch properties of acrylic hard coatings. Issue 5 (18th January 2016) - Chouwatat, Patcharida; Kotaki, Masaya; Miyamoto, Masahiro; Nishimura, Riichi; Yokohama, Atsushi
Abstract : A comparative study of scratch behavior of single‐ and bi‐layer hard coatings deposited on poly(methyl methacrylate) substrates was investigated. Trimethylolpropane triacrylate (TMPTA) and pentaerythriol triacrylate (PETA) with different chemical structure were chosen as a top layer for bilayer coatings, and soft base layer was introduced with varying thickness from 5 to 15 µm to demonstrate effect of soft base layer thickness on scratch properties. The scratch properties were characterized by a progressive load scratch test in terms of the onset of critical normal load for coating failure (i.e., crack and delamination). The introduction of soft base layer caused increase of critical normal load for the onset of coating failures, which implied the excellent scratch properties in both TMPTA and PETA systems. Moreover, it was found that thicker soft base layer led to better scratch properties. POLYM. ENG. SCI., 56:528–535, 2016. © 2016 Society of Plastics Engineers